2021
DOI: 10.22271/tpi.2021.v10.i11z.9139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulphur and Zinc levels on growth and yield of safflower (Carthamus tinctorius L.)

Abstract: A field experiment was conducted during Rabi season 2020 at Crop Research Farm, Department of Agronomy, SHUATS, Allahabad (U.P) to determine the Effect of Sulphur and Zinc levels on growth and yield of spineless safflower. The experiment was laid out in Randomized Block Design, with nine treatments which consisted of viz.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…The increasing in yield might be due to the fact that S perform many physiological functions in Cysteine, methionine and chlorophyll Synthesis.Thus these bioactivities of sulphur might have played important role in improving yield attributing characters and yield of chickpea. Similar results were also given by Patel et al [12], Fayaz et al [13] and Bhuriya et al [14].…”
Section: Yield Of Chickpeasupporting
confidence: 90%
See 1 more Smart Citation
“…The increasing in yield might be due to the fact that S perform many physiological functions in Cysteine, methionine and chlorophyll Synthesis.Thus these bioactivities of sulphur might have played important role in improving yield attributing characters and yield of chickpea. Similar results were also given by Patel et al [12], Fayaz et al [13] and Bhuriya et al [14].…”
Section: Yield Of Chickpeasupporting
confidence: 90%
“…Jadeja et al [15], also reported increased Grain and straw yield of chickpea with sulphur application as compared to control. Similar finding of increased stover yield with sulphur application were also given by Srinivasulu et al [11] Fayaz et al [13] and Bhuriya et al [14].…”
Section: Yield Of Chickpeasupporting
confidence: 84%
“…Plant height might be varied in different crops due to plant spacing; similar findings were also reported by Sefera et al (2021) in mungbean. On the other hand, combination of organic and inorganic fertilizers was created better plant height in groundnut (Mohanty et al, 2022;El-sherbeny et al, 2023) and in green gram (Rajendar et al, 2021) than only inorganic fertilizers application.…”
Section: Plant Heightmentioning
confidence: 94%
“…In addition to protein, mustard oil cake typically contains around 5% nitrogen, which is an essential nutrient for plant growth. The phosphorus content in mustard oil cake ranges from 1.8% to 2.0%, while the potassium content ranges from 1.0% to 1.2% [3].…”
Section: Introductionmentioning
confidence: 99%